2015
DOI: 10.5846/stxb201310142477
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes of Thermal Environment Landscape Pattern in Changsha

Abstract: The urban thermal environment has become the subject of considerable attention in the field of researchinto the eco鄄environmental effects of cities. Research into the laws governing the evolution of the urban thermal environment could contribute to the mitigation of the negative effects of the urban heat island (UHI) and promote the sustainable development of cities. This paper analyzed the spatiotemporal changes of the urban thermal landscape in Changsha, China. Four Enhanced Thematic Mapper Plus thermal imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the one hand, the LST information was obtained from thermal bands and atmospheric parameters; and on the other hand, the land use and cover (industrial land, farmland, woodland), and landscape pattern were derived from optical bands. A correlation analysis was conducted among them to identify the important correlation factors relevant to heat islands [81,85].…”
Section: Remote Sensing Monitoring Of Urban Areasmentioning
confidence: 99%
“…On the one hand, the LST information was obtained from thermal bands and atmospheric parameters; and on the other hand, the land use and cover (industrial land, farmland, woodland), and landscape pattern were derived from optical bands. A correlation analysis was conducted among them to identify the important correlation factors relevant to heat islands [81,85].…”
Section: Remote Sensing Monitoring Of Urban Areasmentioning
confidence: 99%
“…According to landscape ecological theory, the size and shape of these patches also affect their energy accumulation. Likewise, some researchers have recognized that larger patches of construction land have higher degrees of aggregation, more regular shapes, higher LSTs, and more significant heat island effects (Yu, 2006;Fu, 2001;Xie, Wang & Fu, 2011;Xu et al, 2015). Some studies have analyzed different types of disturbances at the interior of mining lands, among which dumps, opencast coal pits, and industrial centers have higher contributions to local warming (Xie, Wang & Fu, 2011;Liu, 2016).…”
Section: Impact Of Coal Mining Activities On Surface Temperaturesmentioning
confidence: 99%
“…In the analysis of the correlation between green landscape spatial configuration and cooling effects, some studies have observed that green patches with simple shapes and concentrated distribution have better cooling effects (Li, et al 2012;Peng, et al 2016;Shuang, et al 2015), while others have concluded that green areas with complex and dispersed shapes have lower temperatures and stronger cooling effects (Li-Hua and Wen-Ze 2008;Yueyi, et al 2014).…”
Section: Introductionmentioning
confidence: 99%